Aromatase inhibitors: assessment of knowledge, adherence, and associated factors among Iraqi women with breast cancer - Bash, Hala Saad; Rabea, Ihsan S. (Pharmakeftiki, 2025)
Adherence to aromatase inhibitors (AIs) as oral anticancer therapy remains a significant challenge in the management of hormone receptor-positive breast cancer. Despite their proven efficacy in reducing disease recurrence, many patients struggle to maintain long-term adherence. This study aimed at evaluating the patients’ knowledge and beliefs regarding AIs and their influence on non-adherence. An observational cross-sectional study was conducted in order to assess adherence and its association with patients’ beliefs, knowledge, and sociodemographic and clinical characteristics. Eligible breast cancer patients receiving AIs (either anastrozole or letrozole) on a monthly basis at the Babylon Oncology Center were recruited between 18 February and 1 October 2024 (N=70). Validated, tailored questionnaires were administered through structured interviews. The mean age of the participants was 56.1 ± 9.6 years. With respect to educational attainment, 48.6% had completed primary school, 25.7% had attained secondary education, 12.9% were illiterate, and 12.9% held a bachelor’s degree. Most patients (98.6%) were married. A majority (62.9%) resided in rural areas, while 37.1% lived in urban settings. Adherence showed a strong positive correlation with the patients’ knowledge of AIs (R=0.638, p<0.001). It was also positively associated with the perceived necessity of therapy (R=0.64, p=0.025), and negatively associated with concerns regarding adverse effects (R=-0.74, p<0.001). These findings suggest that breast cancer patients who exhibit greater awareness and a stronger sense of personal responsibility toward their treatment regimen are more likely to adhere to AI therapy. The study underscores the importance of addressing both perceived benefits and concerns in order to enhance adherence outcomes.